"KOSOVIZATION" OF SERBIAN MONUMENTAL CULTURE AND CREATION OF NEW IDENTITIES (Heritage, 2024)
Starting from the sociological understanding of culture as a set of determinants that channel social movements, the authors analyze the complex Kosovo-Metohija reality with a focus on material monumental heritage and its destruction with the aim of political revision of the past and falsification of Albanian identity. The vandalism of ethnic-religious instrumentalized Albanian groups is concealed by the construction of a media memory of collective memories, which aims at a manipulative strategy of gradually gaining the political support of world opinion. The analysis of characteristic case studies proved the destructiveness of the devastation of the monumental heritage for the Serbian identity, because without the symbolic bearers of the past, the national community that created also disappears. Demolished cemeteries, burned monasteries and churches, with expelled Serbs as bearers of symbolic meaning, opened up space for Albanian nationalists who, by "Kosovizing" Serbian cultural heritage, create their own identity, with the intention of showing that they have always lived in these areas. The theoretical framework is based on British cultural studies that use numerous forms of memorial culture to replace identity and change the culture of memory.
Keywords: Monumental heritage, media memory,